2006
DOI: 10.1002/ajpa.20453
|View full text |Cite
|
Sign up to set email alerts
|

Human skin‐color sexual dimorphism: A test of the sexual selection hypothesis

Abstract: Applied to skin color, the sexual selection hypothesis proposes that male preference for light-skinned females explains the presence of light skin in areas of low solar radiation. According to this proposal, in areas of high solar radiation, natural selection for dark skin overrides the universal preference of males for light females. But in areas in which natural selection ceases to act, sexual selection becomes more important, and causes human populations to become light-skinned, and females to be lighter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 85 publications
4
36
0
Order By: Relevance
“…In light of the acknowledged evolution concepts, it is rather difficult to provide a plausible explanation for this finding; however, there are populations where females are characterized by more pigmented skin, as well as populations characterized by a lack of sexual dimorphism in this feature (Madrigal and Kelly 2007). In contrast to the skin, no dimorphic differences were found in hair pigmentation processes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In light of the acknowledged evolution concepts, it is rather difficult to provide a plausible explanation for this finding; however, there are populations where females are characterized by more pigmented skin, as well as populations characterized by a lack of sexual dimorphism in this feature (Madrigal and Kelly 2007). In contrast to the skin, no dimorphic differences were found in hair pigmentation processes.…”
Section: Discussionmentioning
confidence: 97%
“…In the majority of known populations, females are characterized by lighter pigmentation than males (e.g., Van den Berghe and Frost 1986;Frost 1988;Norton et al 2006;Madrigal and Kelly 2007), which most probably results from the necessity to synthesize a greater amount of vitamin D needed for the periods of pregnancy and lactation (e.g., Jablonski and Chaplin 2000;Parra 2007). This hypothesis is supported by a study of Mazess (1967), who states that female skin is the least pigmented during the reproductive period.…”
Section: Discussionmentioning
confidence: 99%
“…Skin colour varies considerably between people from different regions of the globe but is sexually dimorphic within a specific region, with men having darker (lower L*) and redder (higher a*) skin compared to women (Jablonski & Chaplin, 2000;Russell, 2003;van den Berghe & Frost, 1986). Madrigal and Kelly (2007) analysing the prevalence of sexual dimorphic colour in different areas with different solar radiation, concluded that hormonal factors may be more reliable explanation of differences between sexes. Indeed, according to Hill et al (1995), discrimination of human sexes relies more on colour information than on face shape.…”
Section: Colour As a Sexually Dimorphic Cuementioning
confidence: 99%
“…To address the effect of starting sex on judgements, we included both male and female stimuli. Because skin colour is sexually dimorphic in humans (e.g., Correnti, Testa-Bappenheim, & Granata, 1964; for review, see Madrigal & Kelly, 2007) and macaques (Waitt et al, 2003), we used shape-only transformations to create our stimuli. Next, ±50% of the differences in linear two-dimensional shape between the male and female averages are applied to a third target face (here, our composite faces of either species).…”
Section: Human Perceptions Of Sexual Dimorphism 975mentioning
confidence: 99%